Prokineticins are neuroprotective in models of cerebral ischemia and ischemic tolerance in vitro. (September 2016) - Landucci, Elisa; Lattanzi, Roberta; Gerace, Elisabetta; Scartabelli, Tania; Balboni, Gianfranco; Negri, Lucia; Pellegrini-Giampietro, Domenico E.
Abstract: Bv8/prokineticin 2 (PK2) is a member of a bioactive family of peptides that regulate multiple functions in the CNS including hyperalgesia, neurogenesis, neuronal survival and inflammation. Recent studies have associated PK2 and prokineticin receptors (PKR) with human diseases, but because their role in neuropathology is still debated we examined whether prokineticins exert a protective or deleterious role in models of cerebral ischemia and ischemic tolerance in vitro . In order to mimic cerebral ischemia, we exposed primary murine cortical cell cultures or rat organotypic hippocampal slices to appropriate periods of oxygen-glucose deprivation (OGD), which leads to neuronal damage 24 h later. Ischemic tolerance was induced by exposing hippocampal slices to a preconditioning subtoxic pharmacological stimulus (3 μM NMDA for 1 h) 24 h before the exposure to OGD. Bv8 (10–100 nM) attenuated OGD injury in cortical cultures and hippocampal slices, and the effect was prevented by the PKR antagonist PC7. The development of OGD tolerance was associated with an increase in the expression of PK2, PKR1 and PKR2 mRNA and proteins and was prevented by addition of the antagonist PC7 into the medium during preconditioning. Both Bv8 at protective concentrations and the NMDA preconditioning stimulus promoted the phosphorylation of ERK1/2 and Akt. These findings indicate that the prokineticin system can be up-regulated by a defensive preconditioning subtoxic NMDA stimulus and that PK2 may act as an endogenous neuroprotective factor through the activation of the ERK1/2 and Akt transduction pathways. Graphical abstract: Highlights: Bv8/PK2 are protective in apoptotic and necrotic models of cerebral ischemia. Prokineticins are involved in the development of ischemic tolerance in vitro . Prokineticin neuroprotection is mediated by activation of ERK1/2 and Akt signaling.